Environmental Controls on Nitrogen and Sulfur Cycles in Surficial Aquatic Sediments - Gu, Chuanhui; Laverman, Anniet M.; Pallud, Celine (Frontiers in Microbiology, 2012)
Enhanced anthropogenic inputs of nitrogen (N) and sulfur (S) have disturbed their biogeochemical cycling in aquatic and terrestrial ecosystems. The N and S cycles interact with one another through competition for labile forms of organic carbon between nitrate-reducing and sulfate-reducing bacteria. Furthermore, the N and S cycles could interact through nitrate (NO3-) reduction coupled to S oxidation, consuming NO3- and producing sulfate (SO42-). The research questions of this study were: (1) what are the environmental factors explaining variability in N and S biogeochemical reaction rates in a wide range of surficial aquatic sediments, and (2) which biogeochemical processes are involved when NO3- and/or SO42- are present. The N and S biogeochemical reaction rates were measured on intact surface sediment slices using flow-through reactors. The two terminal electron acceptors (TEA) NO3- and SO42- were added either separately or simultaneously and NO3- and SO42- reduction rates as well as NO3- reduction linked to S oxidation were determined. We used redundancy analysis, to assess how environmental variables are related to these rates. Our analysis showed that overlying water pH and salinity were two dominant environmental factors that explain 58% of the variance in the N and S biogeochemical reaction rates when NO3- and SO42- were both present. When NO3- and SO42- were added separately, however, sediment N content in addition to pH and salinity accounted for 62% of total variance of the biogeochemical reaction rates. The SO42- addition had little effect on NO3- reduction; neither did the NO3- addition inhibit SO42- reduction. The presence of NO3- led to SO42- production most likely due to the oxidation of sulfur. Our observations suggest that metal-bound S, instead of free sulfide produced by SO42- reduction, was responsible the S oxidation. The subsequent release of toxic metals from this coupling might have adverse effects on aquatic ecosystems.